Relevance and Sustainability of "Project Pakigdait sa Sitio Kasagingan, Mananga" of the University of San Jose-Recoletos - Sy, Maria Victoria U. (JPAIR Multidisciplinary Research, 2012)
This study sought to determine the program relevance and sustainability of the institutional community project called "Project Pakigdait sa Sitio Kasagingan, Mananga" of the University of San Jose- Recoletos as assessed by its department anchors, students and program beneficiaries. The respondents were the various stakeholders of the university who were involved in the implementation and supervision of the various programs coming from the different colleges and departments and some selected beneficiaries of the community extension program. The provisions of the program relevance for promoting community development among the community dwellers, promoting people empowerment among adopted community dwellers, and for the conduct of skills training among qualified community members were made to a very great extent. Likewise, the provisions for the sustainability of the project through capacity building were made to a very great extent; however, fund sourcing were made to a great extent.
Keywords: Program relevance; sustainability; people empowerment